Kepatuhan Wajib Pajak Orang Pribadi Usaha Mikro, Kecil, Dan Menengah Ditinjau Dari Tarif Pajak, Sosialisasi Pajak, Sanksi Pajak, Dan Pemeriksaan Pajak - Yogantara, Komang Krishna; Asana, Gde Herry Sugiarto; Clarissa, Sarita Vania (Jurnal Akuntansi Profesi, 2021)
Â Tax has an important role in the economy as the largest source of government funding in carrying out the task of realizing the prosperity of the people. Micro, Small and Medium Enterprises (MSMEs) are one of the sectors that have the potential to contribute large tax payments to state tax revenues. However, the compliance of personal taxpayer of MSMEs still low, especially the compliance of personal taxpayers who are registered in Pratama Tax Office Gianyar has not reached the target of 70 percent. This study aims to determine the influence of the tax rate, tax socialization, tax sanction, and tax investigation toward the obedience of personal taxpayer of Micro, Small, and Medium Enterprises (MSMEs) at the Pratama Tax Office (KPP) Gianyar. Total of 100 MSMEs personal taxpayers that registered at Pratama Tax Office (KPP) Gianyar were selected to be respondents using the Slovin Formula. The research method that used was accidental sampling with media questionnaires andÂ  the technical of analysis data of this study is using multiple linear regression. The conclusion of this study indicate that the tax rate, tax socialization, tax sanction, and tax investigation have positive and significant influence on the obedience of personal taxpayer of MSMEs at Pratama Tax Office (KPP) Gianyar.Keywords: Tax rate, tax socialization, tax sanction, tax investigation